Intersectional research stories of responsibilising the family for food, feeding and health in the twenty-first century. (12th November 2018) - Davis, Teresa; Hogg, Margaret K.; Marshall, David; Petersen, Alan; Schneider, Tanja
Abstract : Purpose: Literature from across the social sciences and research evidence are used to highlight interdisciplinary and intersectional research approaches to food and family. Responsibilisation emerges as an important thematic thread, as family has (compared with the state and corporations) been increasingly made responsible for its members' health and diet. Design/methodology/approach: Three questions are addressed: first, to what extent food is fundamentally social, and integral to family identity, as reflected in the sociology of food; second, how debates about families and food are embedded in global, political and market systems; and third, how food work and caring became constructed as gendered. Findings: Interest in food can be traced back to early explorations of class, political economy, the development of commodity culture and gender relations. Research across the social sciences and humanities draws on concepts that are implicitly sociological. Food production, mortality and dietary patterns are inextricably linked to the economic/social organisation of capitalist societies, including its gender-based divisions of domestic labour.DeVault's (1991 ) groundbreaking work reveals the physical and emotional work of providing/feeding families, and highlights both its class and gendered dimensions. Family mealtime practices have come to play a key role in the emotional reinforcement of the idea of the nuclear family. Originality/value: This study highlights the imperative to take pluri-disciplinary and intersectional approaches to researching food and family. In addition, this paper emphasises that feeding the family is an inherently political, moral, ethical, social and emotional process, frequently associated with gendered constructions.